AL-QUR’AN SEBAGAI SUMBER TEKSTUAL FILSAFAT ISLAM - Syah, Zaimir; Aprison, Wendra (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The main problem in this writing is the Qur'an as a Textual Source of Islamic Philosophy, the main problem is how the position of the Koran is in relation to Islamic philosophy, because the benchmarks for philosophy are reason and revelation. How is the relationship between human (reason), revelation (al-Quran) the basis of philosophy.The purpose of this discussion is the Al-Qur'an as a Textual Source of Islamic Philosophy. The type of research that the writer did was field research which is qualitative description. Data collection techniques that the authors use are through observation, interviews, and documentation. The validity of the data used is triangulation. The analysis technique that the writer uses according to Miles and Huberman. The research results show that knowledge originates from two things: reality and revelation. Reality itself, as in his view, consists of two things, namely metaphysical reality (ma'qulat) giving birth to philosophy and material (mahsusat) giving birth to science. Meanwhile, revelation gave birth to the religious sciences. How to Get to Know/Know Philosophy, namely studying philosophy is no different from studying other sciences.